2002
DOI: 10.1111/j.1741-3737.2002.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Distress and Intimate Violence: Testing Family Stress and Resources Theories

Abstract: Hypotheses shaped by family stress and resource theories about the impact of household economic indicators on the risk of violence against women in intimate relationships are tested with a data set built from the initial two waves of the National Survey of Families and Households (NSFH) and the 1990 U.S. Census. Measures of employment status, job conditions, and economic well‐being for male and female partners are examined with logistic regression analyses as predictors of the odds of male‐to‐female intimate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
218
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(226 citation statements)
references
References 27 publications
8
218
0
Order By: Relevance
“…Results from numerous studies (e.g., Bachman and Saltzman, 1995;Fox et al, 2002;Sorenson et al, 1996;Tjaden and Thoennes, 1998) that have found higher rates of IPV among lower income couples or those experiencing unemployment are consistent with-and lend empirical support to-this theory. In our pilot study analysis of construction workers, we found that couples in which the male construction worker reported being on temporary layoff were at elevated risk for MFPV compared with couples in which the man was not on current layoff (Cunradi et al, 2009b).…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Results from numerous studies (e.g., Bachman and Saltzman, 1995;Fox et al, 2002;Sorenson et al, 1996;Tjaden and Thoennes, 1998) that have found higher rates of IPV among lower income couples or those experiencing unemployment are consistent with-and lend empirical support to-this theory. In our pilot study analysis of construction workers, we found that couples in which the male construction worker reported being on temporary layoff were at elevated risk for MFPV compared with couples in which the man was not on current layoff (Cunradi et al, 2009b).…”
mentioning
confidence: 61%
“…Fox et al (2002) suggest that IPV can be seen as the outcome of an accumulation of stressors in which perceived demands exceed resources, resulting in a crisis expressed through IPV. In this scenario, work stressors might directly associate with IPV behaviors or might interact with IPV norms; work stressors might lead to IPV only among those with positive IPV norms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have linked the stress of unemployment to an increase in family conflict and arguments (Broman, Hamilton, & Hoffman, 1990). Others have found evidence that unemployment is associated with higher levels of marital instability (Starkley, 1996) and intimate violence (Coker, Smith, McKeown, & King,2000;Straus, Gelles, & Steinmetz, 1980), though other researchers have found that the risk of domestic violence is increased due to financial strain, not as a result of unemployment per se (Fox, Benson, DeMaris, & Van Wyk, 2002). Moreover, the stress and tension that result from unemployment and financial hardship can impact children's well-being in both the short and long-term (McLoyd, 1990;McLoyd, Jayaratne, Ceballo, & Borquez, 1994).…”
Section: Background and Prior Researchmentioning
confidence: 99%
“…Research has shown that some intimate relationships suffer from more systematic male violence which is deeply rooted in the patriarchal traditions of men controlling "their" women [8] and that society imparts men with a sense of entitlement to control women within their intimate relationships [9]. Other research using a power inequality perspective indicates that an imbalance of economic resources within couples underlies the use of violence [10]. Better data are needed on gender-based disabilities resulting from factors such as reproductive health, depression, domestic violence, and violence against women.…”
Section: Introductionmentioning
confidence: 99%